A Centimeter‐Scale Inorganic Nanoparticle Superlattice Monolayer with Non‐Close‐Packing and its High Performance in Memory Devices. Issue 27 (21st May 2018) - Wang, Ke; Ling, Haifeng; Bao, Yan; Yang, Mengting; Yang, Yi; Hussain, Mubashir; Wang, Huayang; Zhang, Lianbin; Xie, Linghai; Yi, Mingdong; Huang, Wei; Xie, Xiaolin; et al.
Abstract: Due to the near‐field coupling effect, non‐close‐packed nanoparticle (NP) assemblies with tunable interparticle distance ( d ) attract great attention and show huge potential applications in various functional devices, e.g., organic nano‐floating‐gate memory (NFGM) devices. Unfortunately, the fabrication of device‐scale non‐close‐packed 2D NPs material still remains a challenge, limiting its practical applications. Here, a facile yet robust "rapid liquid–liquid interface assembly" strategy is reported to generate a non‐close‐packed AuNP superlattice monolayer (SM) on a centimeter scale for high‐performance pentacene‐based NFGM. The d and hence the surface plasmon resonance spectra of SM can be tailored by adjusting the molecular weight of tethered polymers. Precise control over the d value allows the successful fabrication of photosensitive NFGM devices with highly tunable performances from short‐term memory to nonvolatile data storage. The best performing nonvolatile memory device shows remarkable 8‐level (3‐bit) storage and a memory ratio over 10 5 even after 10 years compared with traditional devices with a AuNP amorphous monolayer. This work provides a new opportunity to obtain large area 2D NPs materials with non‐close‐packed structure, which is significantly meaningful to microelectronic, photovoltaics devices, and biochemical sensors. Abstract : A facile yet robust "rapid liquid–liquid interface assembly" strategy is reported to generate a non‐close‐packed gold nanoparticle (AuNP) superlattice monolayer (SM) with centimeter scale and tunable interparticle distance. Such SMs are demonstrated for the fabrication of high‐performance photosensitive nano‐floating‐gate memory which shows remarkable 8‐level (3‐bit) storage and a memory ratio over 10 5 .